Controlling a mobile inverted pendulum by nonlinear control method - Đỗ Bình Nguyên; Dương Hoài Nghĩa (Journal of Technical Education Science, 2012)
This paper focuses on controlling a mobile inverted pendulum. Firstly, two methods of linearization were applied to the state equation: feedback linearization and linearization around the operating point. Then, two poles-placement controllers, designed by polynomial method, were used to control the linearized system. Finally, the results by simulating on Matlab – Simulink show that the feedback lineariztion controller is better than the controller which uses the method of linearization around operating point